DETERMINANTS OF SUSTAINABILITY REPORT DISCLOSURE IN INDONESIAN LISTED BANKS - Kezia Kurniawati Tjandrapurnama; Rachmawati Meita Oktaviani (Owner : Riset dan Jurnal Akuntansi, 2023)
The company's achievements cannot be separated from synergies and contributions to support the implementation of digitalization in all lines. To help companies measure and improve performance in managing the company's impact on the environment and society, companies need to report sustainability reports. Sustainability Report is a report issued by the company to report the company's performance that focuses on three main aspects, namely economic aspects, environmental aspects and social aspects. Sustainability reports are issued with the aim of sharing the actions and results of corporate social responsibility. This study aims to examine profitability, sales growth, company size, and the board of commissioners that influence the disclosure of sustainability reports in Indonesia. The population in this study was conducted on 11 companies and obtained 55 samples in the banking sector listed on the Indonesia Stock Exchange (IDX) in 2018 - 2022. The data analysis used is Multiple Linear Regression Analysis. The results of this study state that profitability has a negative effect on disclosure of sustainability reports. Company size has a positive effect on disclosure of sustainability reports. Company age has no effect on disclosure of sustainability reports.